AIR DAN MAKHLUK HIDUP DALAM PERSPEKTIF AL QUR’AN DAN SAINS MODERN - Delta Fitriani; Kholiyah Syafaatunnisa; Alya Nur Zhafira (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2026)
Water is one of the most essential elements for life and has become an important subject of study in both the Qur'an and modern science. This study aims to analyze the concept of water from the perspectives of the Qur'an and modern science and to identify the relationship between the two viewpoints. The research employs a qualitative method with a library research approach. Data were collected through the examination of scientific literature, including books, journal articles, and relevant research findings discussing water in the Qur'an and scientific studies. The results indicate that the Qur'an describes water as the origin of life, a source of divine mercy, and a means of sustaining ecological balance. Meanwhile, modern science explains water as a chemical compound essential for biological processes, environmental stability, and the hydrological cycle. The findings reveal a harmony between Qur'anic explanations and scientific discoveries regarding the role of water in sustaining life. The study concludes that the Qur'an provides theological and spiritual foundations concerning water, while science offers empirical explanations of its characteristics and functions. The integration of these perspectives contributes to a more comprehensive understanding of water as a source of life and a sign of Allah's greatness.